SHAPING STUDENTS’ MODERATE ISLAMIC CHARACTER AT MADRASAH - Ma`arif, Muhammad Anas; Rofiq, Muhamamd Husnur; Kausar, Shakila; Sirojuddin, Akhmad; Kartiko, Ari; Hasan, Moch. Sya'roni (Jurnal Pendidikan Islam, 2024)
The rise of radicalism in educational institutions has prompted urgent concerns about the need for strategies to promote moderate Islamic values, especially in the context of religious education. This research aims to explore how Madrasah Amanatul Ummah fosters the development of a moderate Islamic character among its students. The study employs a qualitative case study approach, utilizing participant observation, interviews, and documentation to gather data. The findings reveal that the madrasah implements a range of strategies, including effective planning, teacher recruitment based on Nahdlatul Ulama (NU) principles, and the integration of moderate Islamic values within both the formal curriculum and institutional culture. These efforts are designed to gradually shape students’ attitudes and behaviors, fostering tolerance, inclusivity, and respect for diversity. The study highlights that cultivating a moderate Islamic character is an ongoing process, with tangible results emerging over time. In conclusion, this research underscores the importance of a holistic and strategic approach to Islamic education, which can contribute to developing an inclusive and tolerant educational system, promoting peace and harmony in diverse societies.